ENHANCING UNSUPERVISED APPROACH FOR PERSON NAME BIPOLARIZATION (International Journal of Engineering and Computer Science, 2014)
A topic is usually associated with a specific time, place, and person(s). Generally, topics that involve bipolar or competing viewpoints are attention getting and are thus reported in a large number of documents. Identifying the association between important persons mentioned in numerous topic documents would help readers comprehend topics more easily. In existing paper propose an unsupervised approach for identifying bipolar person names in a set of topic documents. Specifically, Principal component analysis (PCA) to discover bipolar word usage patterns of person names in the documents, and show that the signs of the entries in the principal eigenvector of PCA partition the person names into bipolar groups spontaneously. To reduce the effect of data sparseness, we introduce two techniques, called the weighted correlation coefficient and off-topic block elimination